Evaluasi Service Operation dan Pembuatan Dokumen Service Strategy Menggunakan Framwork ITIL Versi 3 (Studi Kasus : BPPW Jabar) - zulkifli, ridwan (Jurnal Teknologi dan Bisnis, 2021)
BPPW JABAR (Balai Prasarana Permukiman Wilayah Jawa Barat) under the Ministry of Public Works and Public Housing Directorate General Cipta Karya, is a representative of the Central Government to support the Coordination function with the Regional Government, In the BPPW JABAR organizational structure, there is an Individual Consultant who is placed specifically to deal with obstacles experienced by the organization in the use of IT services, but in its application, there has never been an evaluation for any process of repairing the constraints experienced and documentation for the process of repairing IT service constraints, resulting in every obstacle never experienced repeated with the same case. That is because the number of people who handle IT problems is only 1 person and there is no IT work structure so that work is carried out based on continuous orders, if it continues to occur it will result in obstruction of existing business processes and processes, due to problem handling IT services are not completed quickly and precisely because of the limitations of people and lack of documentation for any problems that have been experienced and resolved. Not just repairing IT service constraints. In the BPPW JABAR organization the dependence on centralized data and secure data storage becomes a high need because every existing data is important and confidential data because it is related to planning data and the implementation of development in the field of Cipta Karya, so the need for an IT service for data storage centralized and can be shared specifically for the work environment of the BPPW JABAR organization and people who have access to the data. The steps taken are evaluating IT services in service operations to assess the level of readiness of the IT problem improvement process experienced by the organization while using IT services and to conduct a GAP analysis between the existing conditions of IT service improvement with the level of maturity expected by the organization in the process of improving IT services and design service strategy for related centralized data and can be shared.